PERBEDAAN RENCANA TANGGAP DARURAT GEMPA BUMI PADA SEKOLAH DASAR DAERAH PESISIR DAN DAERAH PERKOTAAN DI MALANG - Andinawati, Mia; Noorhamdani, Noorhamdani; Hayati, Yati Sri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Indonesia is an earthquake-prone country. The most victim caused by earthquake were school age children. Malang coastal area has 3 times higher earthquake prone than urban area, but urban area has bigger risk of victim and loss. This study aimed to determine differences in earthquake emergency response plans. This research uses observational descriptive with cross sectional design. Population is all principal of elementary school in Malang including coastal and urban area, and sample 34 principal of elementary school in urban area and 34 principal of elementary school in coastal area with purposive sampling. The data were analysed usin Mann-whitney test and significance test using SPSS 16 for windows. The results show that p value (sig)> 0,05 and 1,00 >0,05 wich mean no differences in earthquake emergency response plans. However in coastal area has higher score than urban area. Coastal area has score 10,4 and urban area has score 2,3. Monitoring, reviewing, and updating in earthquake emergency response plans and the development of new initiatives should be built on every school.